Engines of Innovation : The Entrepreneurial University in the Twenty-First Century - Thorp, H. Holden, 1964-; Goldstein, Buck (Book collections on Project MUSE., 2013)
In Engines of Innovation, Holden Thorp and Buck Goldstein make the case for the pivotal role of research universities as agents of societal change. They argue that universities must use their vast intellectual and financial resources to confront global challenges such as climate change, extreme poverty, childhood diseases, and an impending worldwide shortage of clean water. They provide not only an urgent call to action but also a practical guide for our nation's leading institutions to make the most of the opportunities available to be major players in solving the world's biggest problems. A preface and a new chapter by the authors address recent developments, including innovative licensing strategies, developments in online education, and the value of arts and sciences in an entrepreneurial society.